Performance Analysis of DSR and TORA Model Routing Protocols In Vehicular Ad Hoc Network - Sari, Linna Oktaviana; Azmi, Agusurio; Safrianti, Ery; Jalil, Feranita (International Journal of Electrical, Energy and Power System Engineering, 2020)
Pekanbaru city is a large area, therefore traffic congestion often occurs due to the density of society’s vehicles. From this problem, it is needed a technology that can exchange information between vehicles. Information Technology that can involve many vehicles with special network types without dependence on an infrastructure is Ad Hoc Network. One type of this network is Vehicular Ad Hoc Network (VANET). VANET is a new concept in enabling communication between Vehicle to Vehicle (V2V). For efficient data packet delivery, VANET requires a routing protocol. In this research, for simulated and analyzed performance is used the Dynamic Source Routing (DSR) and Temporally Ordered Routing Algorithm (TORA) protocol. NS-2 is used to simulated a moved nodes, SUMO software is used to simulated real map of SKA Mall crossroad and parameter the quality of performance routing protocol DSR can determined by End to End Delay, Packet Delivery Ratio (PDR) and Routing Overhead (RO). This simulation uses scenario 100 nodes, 150 nodes, 200 nodes and 250 nodes. The simulation results with the scenario of changing the number of nodes, the DSR routing protocol produces better performance with an average of End to End Delay is 0.1066 s, average of PDR is 95.45% and average of RO is 1.0076. While the TORA routing protocol has an average of End to End Delay is 0.1163s, average of PDR is 93.49% and average of RO is 1.0801. And in the scenario of node speed changes, the TORA routing protocol produces better performance with an average of End to End Delay is 0.0861 s and average of PDR 97.37%. While the DSR routing protocol is better with an average of RO is 1.0076.